(untitled) (Fiep Bulletin - online, 2014)
The study aims to discuss the content of injuries in bones and articulation in rowing athletes of the sport. Objective: To analyze the habits of paddlers and find out if the rate of injuries is high, low or medium. For this study used a search descriptive of the type of inquiry according to Tomas and Nelson, The sample was 30 (thirty) athletes from professional rowing the male gender of 3 categories of the rowing clubs located in the Rodrigo de Freitas Lagoon in Rio de Janeiro, all practitioners the sports rowing for more than 1 year, without giving any type of injury in bones and articulation at the time of the search and apparently healthy. (ACMS 2006) It was used to collect data a questionnaire which contains 25 questions, with the goal of identifying the legality of the practice of activity and assess the history of diseases and the need for treatment, previously validated for registration and collect the information of the occurrence of injuries in bones and articulation and a bookmark collection of measures and anamnesis. Results: The time devoted to leisure decreased because some athletes are training at full time. Time devoted to feeding increased due to the fact of having to provision the help of a nutritionist to guide them in their diet. Time spent in transit on the ride home-club fell by the fact use the dormitories of the club to pass the night and to go home only on weekends. The vast majority of athletes 66.67% trains in the morning, because of late and studying or working from 9am in the morning, and 33.33% practice activity of rowing, 14h to 18h, because studying in the morning and train in the afternoon. With regard to injuries in bones and articulation, there was a tie, 50% have suffered some kind of injury and 50% reported not. Of the 50% who reported to have suffered some kind of injury or feeling pain after training 33% had lesions in the knee and 27% had problems in the back of the column. It was observed that 57% row two modes, whereas 30% row the two and has no problem of injury. The 27% of respondents who row a parliamentary form of simple, and of these 25% did not have any type of injury. And of the 18% of athletes who row the parliamentary dual 5% did not have any type of injury. Conclusion: With the results shows that it is more beneficial to the rowing athlete of the two current working arrangements, even if it is in the tank training before their health and prevention of injury to the athlete that he only train a mode. Regarding the rate of injury in bones and articulation in rowing athletes of today is the much because of the training outside water than in the training inside the boat, because the injury of knee and the back of the column were made in the training of race and bodybuilding.